IRF5rs2004640 single nucleotide polymorphism is associated with susceptibility to rheumatoid arthritis in South Indian Tamils. Issue 5 (6th October 2014) - Negi, V. S.; Muralidharan, N.; Mehra, S.; Devaraju, P.; Mariaselvam, C. M.; Gulati, R.; Salah, S.; Fortier, C.; Charron, D.; Krishnamoorthy, R.; Tamouza, R.
Abstract Polymorphism of interferon regulatory factor 5 (IRF5), a latent transcription factor gene has been associated with various auto‐immune diseases. Our aim was to study the IRF5rs2004640 gene polymorphism and its association with disease susceptibility, disease phenotype and treatment response in South Indian Tamil patients with rheumatoid arthritis (RA).The study was conducted on 217 RA patients fulfilling the American College of Rheumatology (ACR) 2010 criteria and 482 healthy controls (HCs) without family history of autoimmune disease. The IRF5rs2004640 genotyping was performed using a TaqMan 5′ allelic discrimination assay. We found that the IRF5rs2004640T allele [P < 0.0001, odds ratio (OR) 3.25, 95% confidence interval (CI) 2.55–4.12] and TT genotype (P < 0.0001, OR 4.60, 95% CI 3.23–6.57) were significantly more frequent in RA patients as compared with HCs. No association was found between IRF5rs2004640 polymorphism, clinical manifestations, autoantibody profile and treatment response. IRF5rs2004640 T (mutant) allele may be a susceptibility factor conferring risk for RA in South Indian Tamils, whereas G allele (wild type) may be protective.